Effect of Makeup Use on Depressive Symptoms: An Open, Randomized and Controlled Trial - Marcos C. Veçoso; Souvenir Zalla; Newton Andreo-Filho; Patrícia S. Lopes; Edileia Bagatin; Fernando L. A. Fonseca; Heather A. E. Benson; Vânia R. Leite-Silva (Adis, Springer Healthcare, 2024)
Abstract Introduction Depression is one of the most disabling diseases globally, with a high disease burden that generates high direct and indirect costs. The incidence of depression is twofold higher in adult women than in men. Biological and psychosocial factors constitute the pathophysiological bases of the condition and due to the complexity of the condition, current understanding is that the "treatment strategy must be multimodal". The objective of this study was to measure the effect of introducing the frequent use of makeup on improving depressive symptoms in adult women of medium-low purchasing power Methods Participants with the targeted profile who did not frequently use makeup were selected and randomised to receive (test group) or not (control group) stimuli and makeup products intended for encouraging the frequent use of makeup. The Zung Depression Self-Assessment Scale was used to assess depressive symptoms, with additional assessments on self-image perception using the mirror test and salivary cortisol level. Results The results demonstrated a sustained reduction in depressive symptoms (8.3 percentage points reduction in the Average Zung Index; P < 0.05), with a significant improvement in self-image perception (25% increase in the average score obtained in the mirror test; P < 0.05) and a specific influence on salivary cortisol levels (55% reduction in salivary cortisol concentration; P < 0.05) after the first makeup application. Conclusion The results show that encouraging the frequent use of makeup, a practice that can be achieved by most people and which is simple and inexpensive to implement, can contribute to effective and sustainable improvement in the well-being and mental health of a significant portion of the population.